(untitled) (Our Nature, 2017)
The present work was undertaken to assess the surface water quality and discuss the potability of water by analyzed data of bacteriological (total Coliform and Faecalform) characters and heavy metals content (Fe, Mn, Zn, Pb, Cr and Cu) in the water of Tinau river. The study was carried out in the year 2011/2012 by selecting four spots within three different seasons: winter, summer and rainy. For bacterial enumeration, bacterial plate counts were carried out using the pour plate method with nutrient agar; while for determination of heavy metal concentration, Flame Atomic Absorption Spectro-photometry was used. The heavy metal content was within the range of WHO guideline for drinking purpose. However, on the basis of bacteriological parameters the water was not safe to consume without treatment. This study will also help to make aware those local people or adjacent farmers for proper management of waste disposal and also to minimize use of synthetic inputs.